Abraham and the Multiverse - Fentress-Williams, Judy (Interpretation, 2023)
This article uses a dialogic approach to examine the character of Abraham in Genesis 18 in light of his multiple roles in the story and through the lens of internal family systems theory. The study of the varied characters of Abraham contributes to our understanding of God and the nature of God’s call on Abraham and by extension, our lives.